Le plurilinguisme au cœur de l’action - Anne Morel‑Lab (Recherches en didactique des langues et des cultures)
Ethnolinguistic research led during the construction phases of the big mining projects in New Caledonia, allowed to bring to light the value of a non-standardized plurilingualism, anchored in languages with no economic value. This plurilingualism of the Relation and its didactics which is instrinsically connected to professional activity is the one of "langage go-betweens", administrative assistants of a department dedicated to international mobility of the workforce involved in these big construction projects. As part of the transformation processes of the workforce into a "wordforce", the linguistic capital of these "langage go-betweens" does not lead them to better professional recognition. However, this "didactics of action" questions languages acquisition and transmission practices.